2008
DOI: 10.1038/sj.bdj.2008.981
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of immediate hypersensitivity reaction associated with an amalgam restoration

Abstract: This report describes a case of immediate hypersensitivity reaction associated with the mercury component of amalgam restorations. The release of mercury induced an acute reaction which resulted in erythematous lesions, severe burning and itchy sensation and diffi culty in breathing. Skin patch test results indicated a very strong positive reaction to mercury. Amalgam restorations were replaced with composite fi lling material. The patient, her family and her dental practitioner were strictly advised to use al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Rare cases of assumed immediate generalized hypersensitivity reactions to dental amalgam have also been reported (see for instance Kal, Evcin, Dundar, Tezel, & Unal, 2008;McGivern, Pemberton, Theaker, Buchanan, & Thornhill, 2000).…”
Section: Allergic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare cases of assumed immediate generalized hypersensitivity reactions to dental amalgam have also been reported (see for instance Kal, Evcin, Dundar, Tezel, & Unal, 2008;McGivern, Pemberton, Theaker, Buchanan, & Thornhill, 2000).…”
Section: Allergic Reactionsmentioning
confidence: 99%
“…Tiredness, headaches, pain in muscles and joints, and problems with memory and concentration are among the most frequently reported complaints Lygre, Gjerdet, & Björkman, 2005;Vamnes, Lygre, Grönningsaeter, & Gjerdet, 2004). With the exception of local contact reactions (Al-Hashimi et al, 2007; and rare generalized hypersensitivity reactions (Kal et al, 2008;McGivern et al, 2000), the reported complaints mainly fall into the category of subjectively reported complaints. This means that the complaints, such as pain from muscles and joints, tiredness, headaches and so on, are based on patients' descriptions and cannot be identified through visual inspection, laboratory tests, radiographs et cetera.…”
Section: Patients With Health Complaints Attributed To Dental Amalgammentioning
confidence: 99%
“…(8,11) Contact hypersensitivity reactions are allergic reactions to materials used in dentistry such as amalgam, latex and anaesthetics. (12) The location of the erythematous patch usually corresponds to the site of exposure. (7) Erythematous candidosis is the term given when a candidal infection results in visible red areas on the oral mucosa in the absence of white plaque.…”
Section: Oral Lesionsmentioning
confidence: 99%
“…For instance, Kal et al [26] described an immediate hypersensitivity reaction associated with the mercury component of amalgam restorations. The author reported that the mercury from amalgam fillings induced an acute reaction which resulted in erythematous lesions, severe burning and itchy sensation and difficulty in breathing.…”
Section: Supporting Reportsmentioning
confidence: 99%